To rewrite the equation \(6x^2 = 22x\) in standard form, first, move all terms to one side of the equation:
\[ 6x^2 - 22x = 0 \]
Next, factor out the greatest common factor (GCF) from the left side:
The GCF of \(6x^2\) and \(-22x\) is \(2x\), so we factor it out:
\[ 2x(3x - 11) = 0 \]
Now, we can solve for \(x\) by setting each factor equal to zero:
-
\(2x = 0\)
- Dividing both sides by 2 gives \(x = 0\).
-
\(3x - 11 = 0\)
- Add 11 to both sides: \[ 3x = 11 \]
- Divide by 3: \[ x = \frac{11}{3} \]
Thus, the smaller solution is \(x = 0\), and the larger solution is \(x = \frac{11}{3}\).
Final answers:
- The smaller solution is \(x = 0\).
- The larger solution is \(x = \frac{11}{3}\).